2019
DOI: 10.1021/acs.iecr.9b02580
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Exfoliation of Graphite into Graphene Nanosheets in Elastomer Composites Based on Diels–Alder Reaction during Melt Blending

Abstract: We developed a new technique to in situ exfoliate graphite into graphene nanosheets and simultaneously prepare graphene nanosheets/elastomer composites based on the Diels− Alder (DA) reaction under strong shearing force transferred by the hydrogenated nitrile butadiene rubber (HNBR) during melt mixing. To realize the DA reaction, expanded graphite (EG) was used as a diene and maleic anhydride (MA) was chosen as the dienophile. The results show the efficient functionalization and exfoliation of EG into MA-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The composites were prepared via the simple solution-mixing process between PPMTC and GO (Scheme b). The structure of GO was characterized by Raman spectra (Figure S2b), it is observed that a strong D band at about 1348 cm –1 and a strong G band at about 1600 cm –1 appear in the Raman spectrum, indicating that GO possesses significant structural disorders, , and the ratio of the D band to G band intensities ( I D / I G ) is about 1.15. Figure S2c shows the high-resolution XPS spectra of GO, it could be found that three distinct characteristic peaks corresponding to different functional groups of GO: C–C at 284.7 eV, C–O at 287.2 eV, and COO at 289.1 eV .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composites were prepared via the simple solution-mixing process between PPMTC and GO (Scheme b). The structure of GO was characterized by Raman spectra (Figure S2b), it is observed that a strong D band at about 1348 cm –1 and a strong G band at about 1600 cm –1 appear in the Raman spectrum, indicating that GO possesses significant structural disorders, , and the ratio of the D band to G band intensities ( I D / I G ) is about 1.15. Figure S2c shows the high-resolution XPS spectra of GO, it could be found that three distinct characteristic peaks corresponding to different functional groups of GO: C–C at 284.7 eV, C–O at 287.2 eV, and COO at 289.1 eV .…”
Section: Results and Discussionmentioning
confidence: 99%
“…For the composites, the significant increase in stress is observed at about 330 and 300% for the PPMTC/GO0.1 and PPMTC/GO-GO0.3 samples, respectively; no obvious upturn in stress is found for PPMTC/GO1 until its ultimate rupture. The possible reason for the upturn of tensile stress in a certain tensile strain is the orientation of PPMTC mainchains or the strain-induced crystallization, , the orientation or the PPMTC crystallites acted as the reinforcing filler; a further study will be carried out to clarify the mechanism of the significant increase of stress for the PPMTC.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the Diels-Alder reaction has been employed to chemically exfoliate graphite to obtain graphene and its analogs. In 2019, Tian [27] developed a method to exfoliate graphite in situ, in rubber and graphite blends, into graphene nanosheets based on the Diels-Alder reaction under strong shearing force. However, in the above methods, the exfoliation of graphite required strong shear force, and the thickness of the resultant exfoliated graphite was only reduced to the range of 0.1-1 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a typical “2D material” in that it is a form of carbon with a single atomic layer thickness composed of an sp 2 hybrid structure . In the past decade, graphene has been widely explored in academia and industry due to its compelling features, such as an extraordinarily large specific surface area, ultrahigh strength, and excellent conductivity. , Consequently, graphene has become a promising filler candidate for rubber composites. Among the preparation methods used for graphene/rubber composites, green latex compounding is an efficient method for the industrialization of achieving uniform dispersion of graphene and further improving the comprehensive properties of rubber composites. , However, the prerequisite for implementing the method is that both graphene and rubber molecular chains must be stably dispersed in the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%